ERAP2 Is Associated With Immune Infiltration and Predicts Favorable Prognosis in SqCLC - Yang, Zhenlin; Tian, He; Bie, Fenglong; Xu, Jiachen; Zhou, Zheng; Yang, Junhui; Li, Renda; Peng, Yue; Bai, Guangyu; Tian, Yanhua; Chen, Ying; Liu, Lei; et al. (Frontiers in Immunology, 2021)
Background Immunotherapy has been proven effective among several human cancer types, including Squamous cell lung carcinoma (SqCLC). ERAP2 plays a pivotal role in peptide trimming of many immunological processes. However, the prognostic role of ERAP2 and its relationship with immune cell infiltration in SqCLC remains unclear. Methods The differential expression of ERAP2 was identified via GEO and TCGA databases. We calculated the impact of ERAP2 on clinical prognosis using the Kaplan-Meier plotter. TIMER was applied to evaluate the abundance of immune cells infiltration and immune markers. SqCLC tissue microarrays containing 190 patients were constructed, and we performed immunohistochemical staining for ERAP2, CD8, CD47, CD68, and PD-L1 to validate our findings in public data. Results In the GEO SqCLC database, ERAP2 was upregulated in patients with better survival (p=0.001). ERAP2 expression in SqCLC was significantly lower than that of matched normal samples (p<0.05) based on TCGA SqCLC data. Higher expression of ERAP2 was significantly associated with better survival in SqCLC patients from TCGA (p=0.007), KM-plotter (p=0.017), and our tissue microarrays (TMAs) (p=0.026). In univariate and multivariate Cox analysis of SqCLC TMAs, high ERAP2 expression was identified as an independent protective factor for SqCLC patients (Univariate Cox, HR=0.659, range 0.454-0.956, p<0.05. Multivariate Cox, HR=0.578, range 0.385-0.866, p<0.05). In TIMER, ERAP2 was positively correlated with several immune markers (CD274, p=1.27E-04; CD68, p=5.88E-08) and immune infiltrating cells (CD8+ T cell, p=4.09E-03; NK cell, p=1.00E-04). In our cohort, ERAP2 was significantly correlated with CD8+ tumor-infiltrating lymphocytes (TILs) (p=0.0029), and patients with higher ERAP2 expression had a higher percentage of PD-L1 positive patients (p=0.049) and a higher CD8+ TILs level (p=0.036). Conclusions For the first time, our study demonstrates that higher expression of ERAP2 is tightly associated with the immuno-supportive microenvironment and can predict a favorable prognosis in SqCLC. Meanwhile, ERAP2 may be a promising immunotherapeutic target for patients with SqCLC.